Where Numbers Fall Short: Realities of Medical and Critical Illness Claims in Nepal’s Insurance Sector (Journal of Insurance Studies in South Asia, 2025)
Nepal’s insurance sector is undergoing rapid transformation, particularly in health and critical illness coverage. However, a growing gap exists between product design and real-world claim adjudication. This article examines the inconsistencies between actuarial assumptions, medical realities, and policy interpretations within Nepal’s insurance landscape. Drawing from five years of practitioner-based experience in both life and general insurance claims, the study utilizes qualitative case analysis to highlight systemic weaknesses in claim settlement, including diagnostic ambiguities, definitional rigidity, and documentation discrepancies. Six anonymized case studies illustrate recurring issues such as denial due to technical policy wording, absence of standardized medical documentation, and lack of coordination between claims, underwriting, and actuarial teams. The findings emphasize the need for localized policy definitions, standardized documentation, feedback integration, and regulatory oversight. The paper concludes that bridging actuarial precision with operational sensitivity is vital for strengthening customer trust and establishing an equitable, context-sensitive insurance ecosystem in Nepal.